The Effect of Financial Literature, Electronic Money, Self-Control, and Lifestyle On Student Consumption Behavior - Ni Made Wike WIDIYANTI; I Made SARA; Ita Sylvia Azita AZIZ; I Gusti Ayu Athina WULANDARI (Journal of Tourism Economics and Policy, 2022)
Consumptive behavior of the Undergraduate Faculty of economics and business at the University of Warmadewa is certainly influenced by internal and external students condition. Consumptive behavior level can be influenced by many factors. This study aims to determine the effect of Financial Literacy, Electronic Money, Self Control, and Lifestyle on Student Consumptive Behavior of Faculty Economics and Business University of Warmadewa. The object of this research is the Undergraduate Faculty of Economics and Business University of Warmadewa., with a 5394 population. The sample in this study amounted to 98 people determined by the Solvin formula. The analytical method used is descriptive analysis and multiple linear regression. The results of this study showed that, Financial Literacy, Electronic Money, Lifestyle, and Self Control, simultaneously have a significant effect at = 0.05 on Student Consumptive Behavior. Partially, at = 0.05 the variables of Financial Literacy and Electonic Money have a negative and not significant effect on Consumptive Behavior, while the variables of Self Control and Lifestyle have a positive and significant effect on Consumptive Behavior. Partially, financial literacy has a positive and insignificant effect on consumptive behavior in students of the Faculty of Economics and Business, Warmadewa University. Partially, electronic money has a positive and insignificant effect on consumptive behavior in students of the Faculty of Economics and Business, Warmadewa University. Partially, self-control has a positive and significant effect on consumptive behavior in students of the Faculty of Economics and Business, Warmadewa University.